Kajian Nilai “Satyam” Dalam Film “Snowden” (Sebuah Analisis Semiotika Roland Barthes) - I Made Bagus Andi Purnomo (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Very rapid development of the era resulted in education not only limited to class meetings. But also penetrated the digital world. The main community of the young generation is very fond of learning through social media. Starting from google, youtube, movies and also various other digital references. However, not all digital facilities, one of which is film that provides educational content that is able to have an impact on changing the character of the younger generation to the better. Mostly only love films and even penetrated in films that should not have been watched by children (sexuality). On this basis, this research was conducted to examine one of the films in the public spotlight namely the film